(untitled) (World Bulletin of Public Health, 2023)
The main pathophysiological mechanisms underlying the potential use of anti-rheumatic therapy in case of the new coronavirus infection COVID-19 in patients with rheumatic diseases (RD) are described, as well as current data on the risk and outcome of COVID-19 in patients with systemic autoimmune diseases are summarized in the overview of the article. Currently there are no wide range of randomized trials studying the use of antirheumatic medication in patients with RD associated with a new coronavirus infection. Besides, there is no convincing evidence that any disease-modifying anti-rheumatic medication (usually synthetic, biological or targeted synthetic) can prevent the progress of severe course of COVID-19. At the same time, the relevance of accompanying pathology (arterial hypertension, obesity, cardiovascular diseases, diabetes mellitus) and risk factors (smoking) are shown in the progress of a severe course of a new coronavirus infection in patients with RD. The article presents possible options for initiation and continue therapy with antirheumatic medication in patients with RD, depending on the stage of the infectious process.